Pentraxin 3 is up-regulated in epithelial mammary cells during Staphylococcus aureus intra-mammary infection in goat. (August 2018) - Filipe, J.; Curone, G.; Bronzo, V.; Pisoni, G.; Cremonesi, P.; Pollera, C.; Turin, L.; Vigo, D.; Roccabianca, P.; Caniatti, M.; Moroni, P.; Riva, F.
Highlights: PTX3 nucleotide sequence is highly conserved among the species. PTX3 is mainly expressed in goat bone marrow mammary gland aorta rectum pancreas skin. The infected udder influences the inflammation in the contralateral healthy one. Staphylococcus aureus intra-mammary infection causes systemic and local PTX3 modulation. Abstract: Pentraxin 3 is the prototypic long pentraxin and is produced by different cell populations (dendritic cells, monocytes/macrophages, endothelial cells, and fibroblasts) after pro-inflammatory stimulation. Different studies demonstrated the up-regulation of PTX3 during mastitis in ruminants, but its role is still unknown. We first investigated the conservation of PTX3 sequence among different species and its pattern of expression in a wide panel of organs from healthy goats. We studied the modulation of PTX3 during natural and experimental mammary infection, comparing its expression in blood, milk and mammary tissues from healthy and Staphylococcus aureus infected animals. We confirmed the high conservation of the molecule among different species. Goat PTX3 was expressed at high levels in bone marrow, mammary gland, aorta, rectum, pancreas, skin and lungs. PTX3 was up-regulated in epithelial mammary cells and in milk cells after S. aureus infection, suggesting that it represents a first line of defense in goat udder.